Induced expression modes of genes related to Toll, Imd, and JAK/STAT signaling pathway-mediated immune response in Spodoptera frugiperda infected with Beauveria bassiana - Li, Jihu; Mao, Yongkai; Yi, Jiequn; Lin, Mingjiang; Xu, Hanliang; Cheng, Yinjie; Wu, Han; Liu, Jianbai (Frontiers in Physiology, 2023)
Spodoptera frugiperda is one of the most harmful pests that attack maize and other major food crops and causes huge economic loss every year in China and other countries and regions. Beauveria bassiana, a kind of entomological fungus that is highly pathogenic to pests, is harmless to the environment and human beings. However, at present, S. frugiperda has gradually developed resistance to many pesticides and microbial insecticides. In this study, transcriptome sequencing was conducted to analyze the differences in gene expression between B. bassiana-infected and -uninfected S. frugiperda. More than 160 Gb of clean data were obtained as 150-bp paired-end reads using the Illumina HiSeq™ 4000 platform, and 2,767 and 2,892 DEGs were identified in LH36vsCK36 and LH144vsCK144, respectively. In order to explore the roles of JAK/STAT, Toll, and Imd signaling pathways in antifungal immune response in S. frugiperda against B. bassiana infection, the expression patterns of those signaling pathway-related genes in B. bassiana-infected S. frugiperda were analyzed by quantitative real-time PCR. In addition, antifungal activity experiments revealed that the suppression of JAK/STAT, Toll, and Imd signaling pathways by inhibitors could inhibit the antifungal activity to a large extent and lead to increased sensitivity of S. frugiperda to B. bassiana infection, indicating that JAK/STAT, Toll, and Imd signaling pathways and their associated genes might be involved in the synthesis and secretion of antifungal substances. This study implied that JAK/STAT, Toll, and Imd signaling pathways played crucial roles in the antifungal immune response of the S. frugiperda larvae, in which the related genes of these signaling pathways could play special regulatory roles in signal transduction. This study would improve our understanding of the molecular mechanisms underlying innate immunity and provide the basis for a wide spectrum of strategies against antifungal resistance of S. frugiperda.